2018
DOI: 10.1007/s12671-017-0879-7
|View full text |Cite
|
Sign up to set email alerts
|

Validating of the Interpersonal Mindfulness in Parenting Scale in Hong Kong Chinese

Abstract: Mindful parenting (MP) is an emerging concept that refers to parenting in which practices and principles of mindfulness are integrated into parents' thoughts, feelings, and behaviors. In particular, attitudes of compassion, acceptance, and kindness are emphasized in interactions with children (Bogels & Restifo, 2015;Duncan et al., 2009; Kabat-Zinn & Kabat-Zinn, 1997). Although it is possible to use behavioral observation to assess MP (Duncan et al., 2015), it is more common and convenient to use self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 58 publications
3
42
1
6
Order By: Relevance
“…We also did not find any differences between fathers and mothers in mindful parenting behavior, which was not consistent with most previous studies that have found that mothers exhibit higher levels of mindful parenting than fathers in Western countries (e.g., Moreira and Canavarro 2015;Pan et al 2019;Parent et al 2015). However, preliminary research on mindful parenting behaviors of Chinese parents demonstrated that no gender discrepancy existed (e.g., Han et al 2019;Lo et al 2018). These results might be explained by the core values in Chinese culture that emphasize the integral parenting roles of both mothers and fathers in child development despite each role having different responsibilities.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…We also did not find any differences between fathers and mothers in mindful parenting behavior, which was not consistent with most previous studies that have found that mothers exhibit higher levels of mindful parenting than fathers in Western countries (e.g., Moreira and Canavarro 2015;Pan et al 2019;Parent et al 2015). However, preliminary research on mindful parenting behaviors of Chinese parents demonstrated that no gender discrepancy existed (e.g., Han et al 2019;Lo et al 2018). These results might be explained by the core values in Chinese culture that emphasize the integral parenting roles of both mothers and fathers in child development despite each role having different responsibilities.…”
Section: Discussioncontrasting
confidence: 88%
“…A 5-point Likert scale ranging from 1 = never true to 5 = always true was used. The Hong Kong (Chinese) version of the IM-P has shown good validity and internal consistency in Chinese Hong Kong parents (Lo et al 2018). For parents of children with ASD in the current study, the Cronbach's alphas were 0.71, 0.70, 0.66, and 0.87 for the LAF, EAP, NJAP, and CC subscales, respectively.…”
Section: Mindful Parentingmentioning
confidence: 54%
“…Interpersonal Mindfulness Parenting Mindful parenting was measured using the composite score from the Interpersonal Mindfulness in Parenting (IM-P; Duncan et al 2009). The Chinese version of the IM-P, which has been good psychometric properties, was used (Lo et al 2018). The 31-item version is comprised of five subscales corresponding to the different dimensions of mindful parenting: (1) listening with full attention (e.g., I find myself listening to my child with one ear because I am busy doing or thinking about something else at the same time); (2) emotional awareness of self and child (e.g., I notice how changes in my child's mood affect my mood); (3) self-regulation in the parenting relationship (e.g., When I am upset with my child, I notice how I am feeling before I take action); (4) non-judgmental acceptance of self and child (e.g., I try to understand my child's point of view, even when his/her opinions do not make sense to me); and (5) compassion for self and child (e.g., I tend to be hard on myself when I make mistakes as a parent).…”
Section: Methodsmentioning
confidence: 99%
“…Having considered that mindfulness influences relational functioning, we turn to the research on whether mindfulness in family members affects the mental and physical health, and reduces symptoms of (psycho)pathology of the individual, starting with parents. There is a large body of recent cross-sectional evidence showing that higher dispositional mindful parenting is associated with lower child (psycho)pathology: with parent-reported adolescents' anxiety and depression [23] with parent-reported child behavior problems [24] with adolescents' risk behaviors substance abuse and sexual engagement [25] with parent-reported youth internalizing and externalizing problems across three developmental stages [26] and youth-reported mindful parenting in fathers…”
Section: Mindfulness Affecting Health Of Family Membersmentioning
confidence: 99%